Application of dynamic thermal engineering principles to improve the efficiency of resource use in UK pork production chains - Jackson, Paul; Guy, Jonathan; Edwards, Sandra A.; Sturm, Barbara; Bull, Steve (Energy and buildings, 2017)
This paper investigates the potential for incorporation of human commercial building design modelling into the pig production industry. During the last decades pig building design has relied heavily on building manufacturers compared to human commercial buildings that regulate standards to improve the sustainability of the building. Thus, the aim of this paper was to gain a greater understanding of the design requirements for sustainable forms of pig housing, which could potentially improve the welfare of the pig and promote greater resource use efficiency. Part of an existing mechanically ventilated UK pig production building, which represents three adjacent fully-slatted units each capable of holding approximately 292 pigs and measuring approximately 18m x 14m, was used as a basis to create a dynamic thermal model of the building. The model takes into account the possibility of future rises in environmental temperature and the effect of this climate change on building performance and pig growth, feed efficiency and welfare. The results of the model showed that as the finishing pigs increased in size they have the potential to be subject to increasingly poor indoor air quality, during the winter months. The model also shows that improving the thermal properties of the building not only helps with reducing the amount of time that the pigs could potentially spend at extreme low temperatures, by approximately 1115h (46days), but can also help with reducing the number of hours the pigs spend above 26°C during the summer months, by approximately 8h.